2019
DOI: 10.3390/nu11081851
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Conception Maternal Food Intake and the Association with Childhood Allergies

Abstract: Background: Periconceptional nutrition may have an important function in programming the immune function and allergies, however, there is a lack of studies assessing pre-conception food intake and childhood allergic disorders. The aim of the current study was to identify maternal pre-conception dietary components that may be associated with allergic disorders in children up to 3 years of age. Methods: Pregnant women attending their first antenatal visit and who were aged >18 years were invited to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
3
5
0
Order By: Relevance
“…We also found that mothers of infants with eczema consumed more protein from poultry food source during pregnancy than mothers of infants without eczema. This result was in line with a previous study in Australia demonstrating that maternal pre-conception poultry intake was positively associated with offspring eczema ( 56 ). In the adult literature, two studies also found that diets with high intake of poultry were associated with allergic diseases ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that mothers of infants with eczema consumed more protein from poultry food source during pregnancy than mothers of infants without eczema. This result was in line with a previous study in Australia demonstrating that maternal pre-conception poultry intake was positively associated with offspring eczema ( 56 ). In the adult literature, two studies also found that diets with high intake of poultry were associated with allergic diseases ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 93%
“…There is increasing recognition of the importance of nutrition for reproductive health [4]. Observational studies have consistently shown associations between poorer food choices or unhealthier dietary patterns and higher risk for infertility [5][6][7], gestational diabetes (reviewed in [8,9]) and preterm birth [10], but also contributing to poorer outcomes for the offspring, including increased risk for low birth weight [11], child allergy [12], and child adiposity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Saturated spreads (e.g., butter) were protective against eczema, current wheeze, and rhinitis, while non-oily fish was protective against eczema and current wheeze; however, poultry and fruit juice were adversely associated with allergies. The authors, however, emphasize that this topic requires further research [ 19 ]. Nonetheless, these results coincide with the false alarm hypothesis, which suggests that food allergy is associated with high intake of advanced glycation end-products (AGEs) and proglycating dietary sugars that may work as alarmins—endogenous molecules secreted from cells undergoing nonprogrammed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been also mentioned that the limitation might have been the use of self-reported food frequency questionnaires (FFQs) to assess food intake, possibly leading to errors caused by subject memory bias. Another study, dedicated to maternal pre-conception food intake, such as low and high fat dairy, fresh fruit, saturated and unsaturated spreads, and take-away foods, revealed some protective impact for several atopic diseases but at the same time poultry and fruit juice were adversely associated with eczema, current wheeze and rhinitis classified as “each allergy” [ 19 ]. That study was also limited by FFQs and maternal group characteristic showing that almost 30% were obese and 50% were asthmatic.…”
Section: Introductionmentioning
confidence: 99%